Comparative Efficacy of Treatment Options for Prevention of Post-TIPS Hepatic Encephalopathy: : A Systematic Review and Network Meta-analysis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Research